Make it an Occasion! With Plastics Housewares Made of Styron - Dow Chemical Company (1949)
Color print advertisement for Styron, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications. The advertisement features a party scene of four adults at a table in front of a fireplace. A woman is serving food on plastic plates. Below are illustrations of different housewares made from Styron. The accompanying text provides details for the illustrated items and promotes the use of "gay colored housewares" made from Styron. This advertisement appeared on page 161 of a 1949 edition of Ladies' Home Journal.
Keywords: Dow Chemical Company; Advertising; Chemical industry; Corporations; Plastics; Plastics industry and trade; Housewives as consumers; Women in advertising; Entertaining; Advertising, Industrial; Consumer goods